FINANCIAL AND NON-FINANCIAL FACTORS INFLUENCING INTERNET FINANCIAL AND SUSTAINABILITY REPORTING (IFSR) IN INDONESIA STOCK EXCHANGE - Luciana Spica Almilia (Faculty of Economics and Business, Universitas Gadjah Mada, 2010)
Internet Financial and Sustainability Reporting (IFSR) is voluntary in nature. With no specific regulations on IFSR, there is a disparity of IFSR practices among companies.Some companies disclose only partial financial statement using a low level of technology, while others disclose full sets of financial reports using sophistications of the web such as multimedia and analytical tools. Sustainability (1999) addressed the benefits (global reach, immediacy, ease of updating, transparency, link ability, and interactivity) ofreporting social and environmental information on the website and thus the factors that affect decision of whether or not to use this communication medium. By placinginformation on the firm’s website, users can search, filter, retrieve, download, and even reconfigure such information at low cost in a timely fashion.The purpose of this study was to examine financial variables that affect Internet Financial and Sustainability Reporting (IFSR) of listed in Indonesia Stock Exchange companies. The ordinal logistic regression used to examine variables that affect Internet Financial and Sustainability Reporting (IFSR). The sample of this research is companies that listed in Indonesia Stock Exchange. The 203 observations were divided into three categories: 87 companies not providing financial and sustainability report in the internet (No website), 62 companies providing financial and sustainability report in the internet with low index (Low Index) and 54 companies providing financial and sustainability reportin the internet with high index (High Index). The result shows that firm size, majority shareholders, auditor size and industry type as a determinant factor of internet financialand sustainability-reporting index in Indonesia, whereas leverage and profitability not statistically significant as determinant factors of internet financial and sustainabilityreporting index in Indonesia.Keywords: internet financial reporting, website, traditional financial reporting, internet, financial statement, voluntary disclosure.